2009
DOI: 10.1021/ol9023387
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyldiimidazole-Mediated Lossen Rearrangement

Abstract: Carbonyldiimidazole (CDI) was found to mediate the Lossen rearrangement of various hydroxamic acids to isocyanates. This process is experimentally simple and mild, with imidazole and CO(2) being the sole stoichiometric byproduct. Significant for large-scale application, the method avoids the use of hazardous reagents and thus represents a green alternative to standard processing conditions for the Curtius and Hofmann rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(59 citation statements)
references
References 37 publications
1
56
0
2
Order By: Relevance
“…We found that the desired product could be synthesized by nucleophilic addition of benzylamine to 1,4,2-dioxazol-5-one, 8 (Scheme 2). 39 The reaction was indeed completely O -selective, affording 6a as the sole product in high yield (88%). Encouraged by this result, intermediate 8 was reacted with a variety of amines to provide carbamate prodrugs 6a - l (Scheme 2).…”
Section: Resultsmentioning
confidence: 90%
“…We found that the desired product could be synthesized by nucleophilic addition of benzylamine to 1,4,2-dioxazol-5-one, 8 (Scheme 2). 39 The reaction was indeed completely O -selective, affording 6a as the sole product in high yield (88%). Encouraged by this result, intermediate 8 was reacted with a variety of amines to provide carbamate prodrugs 6a - l (Scheme 2).…”
Section: Resultsmentioning
confidence: 90%
“…A most recent method for the synthesis of carbamates 6 through the reaction of hydroxamic acids 163 with an alcohol 5 using carbonyl diimidazole (CDI) through Lossen rearrangement was reported by Dube and coworkers (Scheme 145) [210]. …”
Section: 7c Lossen Rearrangementmentioning
confidence: 99%
“…Alternatively, the Lossen rearrangement provides access to isocyanates under relatively mild conditions. To date, several synthetic methods have been developed for the synthesis of ureas through Lossen rearrangement, for example, phosgene and its derivatives such as triphosgene [7] are widely used reagents for synthesis of ureas; together with chloroformates, [8] cyanuric chloride, [9] 1,1'-carbonyldiimidazole, [10] 1-propanephosphonic acid cyclic anhydride (T3P), [11] N,N'-dicyclohexylcarbodiimide, [12] Nbenzyl-N'-(3-dimethylaminopropyl)carbodiimide, [13] Zr(IV)-catalyst, [14] Pd-catalyzed [15] and 2-chloro-1-methylpyridinuim iodide. [16] On the other hand, Boc-Oxyma (I, Ethyl 2-(tertbutoxycarbonyloxyimino)-2-cyanoacetate, Figure 1) Figure 1.…”
Section: Introductionmentioning
confidence: 99%